Implementation of Push Notification for Monitoring Motor Vehicle Tax Payments (Case Study: Samsat Siak) - Herwin herwin; Khusaeri Andesa (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2023)
In an effort to maximize revenue from the motor vehicle tax, the local government is pursuing numerous strategies, one of which is to introduce the e-Samsat (PAD) program to increase revenue from the motor vehicle tax. However, in the current system, there is no system to monitor these payments. Therefore, many people pay their taxes late. The objectives of this research are: (1) Design and develop a web-based application to monitor tax payments using Whatsapp gateway. Data collection techniques using interviews and direct observation at the research site. The results of this application research can display a list of taxpayers and can add to the list of taxpayers. It also generates outputs in the form of data reports in various forms and types. Designing an application to process vehicle tax data makes it easier for employees to detect late tax payments. The public can learn about tax payments via WhatsApp notifications without having to visit Samsat Siak.